Can TAVI be performed without on-site cardiac surgery? - V. Lodo; C. Barbero; S. Salizzoni; E. Zingarelli; M.La Torre; Italiano G. Enrico; P. Centofanti; M. Rinaldi (International Journal of Cardiology: Heart & Vasculature)
Introduction: Aim of this analysis in to assess the prevalence and post-procedural outcomes of surgical bailout during transcatheter aortic valve implantation (TAVI). Methods: Patients undergoing TAVI from September 2017 to March 2023 were enrolled from two high volume centers. All the procedures were performed with on-site cardiac surgery, but especially the scrubbed cardiac surgeon. The primary endpoint was in-hospital mortality of TAVI patients after emergent cardiac surgery (ECS). Secondary endpoints were intra-operative and 1-year mortality, and post-procedural complications such as acute kidney injury (AKI), stroke, myocardial infarction (MI), conduction abnormalities, need for inotropic support and intensive care unit (ICU) and in- hospital length of stay. Results: A total of 1347 consecutive patients underwent transfemoral TAVI. Ten patients (0.74 %), representing the study population, reported intra-procedural complications requiring ECS: seven patients received a self-expandable prosthesis; three patients received a balloon expandable prosthesis. Indications for ECS included: type A dissection (n = 2), aortic annulus rupture (n = 1), left(n = 1) and right (n = 2) ventricle perforation, mitral valve apparatus damage (n = 2), prosthesis embolization (n = 2). Four patients required post-operative inotropic support. One case of minor stroke and one case of AKI (grade III) were reported. Three patients developed a post procedural left bundle branch block (LBBB). Median ICU and hospital length-of-stay were 4.5 (2–7.75) days and 14 (8–22) days, respectively. One case of in-hospital mortality was reported. Conclusions: The on-site cardiac surgery, with the scrubbed heart surgeon, represents a life-saving resource for TAVI centers in case of ECS, and it is essential to achieve low-rate in-hospital mortality.